Stability and Seakeeping of Marine Vessels - Begovic, Ermina; Mancini, Simone; Begovic, Ermina; Mancini, Simone (Basel, Switzerland MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book presents the papers accepted into the Special Issue (3z(BStability and Seakeeping of Marine Vessels(3y (Band includes nine contributions to this Special Issue published in 2020. The overall aim of the collection is to improve knowledge about the most relevant and recent topics in ship stability and seakeeping. Specifically, the articles cover a wide range of topics and reflect the recent scientific efforts in the 2nd generation intact stability criteria evaluation and modelling of the ship dynamics assessment in intact or damaged conditions. These topics were investigated mainly through direct assessments performed both via numerical methods and tools, and experimental approaches. The book is addressed to individuals from universities, research organizations, industry, government agencies and certifying authorities, as well as designers, operators and owners who contribute to improved knowledge about (3z(Bstability and seakeeping(3y(B.s
English
Keywords: Technology: general issues; URANS; VOF; overset mesh; side damage; bottom damage; flooding process; motion response; nonlinear steady flow; desingularized Rankine panel method; forward speed; radiation and diffraction; adaptive weather routing; Seakeeping Performance Index; route optimization; Dijkstra algorithm; Cummins equations; vertical motions assessment; time domain simulations; experimental seakeeping; hard chine displacement hull form; second generation intact stability criteria; operational guidance; operational limitations; vulnerability levels; direct stability assessment; Ro-Ro ferry; coastal patrol ship (CPS); full-scale seakeeping trials; ship design; barge platform; zero-pressurized air cushion; hydrodynamic performance; boundary element method; container ship; added resistance in waves; sea states; potential flow theory; variation of ship characteristics; strip theory; BEM; RANS; regular wave; seakeeping; n/a